Evaluation of measurement dose uncertainty of gafchromic EBT3 because of local inhomogeneity - Sukhikh E. S. Evgeniya Sergeevna; Sukhikh L. G. Leonid Grigorievich; Malikov E. L. Evgeny Lvovich (L'vovich); Filatov P. V. Peter Valerjevich (2016, 2016)
В фонде НТБ ТПУ отсутствует